The age of Lincoln - Burton, Orville Vernon (New York Hill and Wang, 2007)
"In a remarkable reappraisal of Lincoln, distinguished historian Burton shows how the Kentucky-born president?s Southernness empowered him to conduct a civil war that redefined freedom as a personal right protected by the rule of law. In the violent decades that followed, the extent of that freedom would be contested by racism and unregulated capitalism, but not its central place in what defined the country"--From publisher description.
Keywords: Lincoln, Abraham -- 1809-1865.; Reconstruction (U.S. history, 1865-1877); United States -- History -- 19th century; United States -- History -- Civil War, 1861-1865.